Religious leaders and provincial governors aspired to the throne in Egypt until the end of the Sixth Dynasty 3200 - 2280 BC. M (Journal of the College of Basic Education, 2022)
The political system in Egypt, which is nearly 3000 years old, has gone through difficult political stages ranging from the power of the central state, which was the dominant feature of the kingship from the first dynasty to the fourth dynasty, but this did not last long. Difficult historical changes since the end of the Fourth Dynasty, and reflected on the political system of government, lost their central state after the thorns of priests and governors of the provinces. This paper traces the political circumstances that contributed to the undermining of this system.